Complete Load Analysis of a residential Hall of CUET in Bangladesh and Design of a Roof Top Solar PV System - Md. Shamsul Arifin; M. Tariq Iqbal (IAES Indonesian Section, 2021)
In this paper a complete load analysis of a residential hall of CUET in Bangladesh is performed, and a roof top solar PV System is designed. At first the load of this building is estimated, and a complete daily load profile is developed. Using the estimated load profile, the size of solar array and other components are estimated. After that, a complete system is designed connecting the components of estimated rating and size. Additionally, an optimization of system is performed using HOMER. Furthermore, the dynamic response of the proposed system is analyzed using Simulink, MATLAB and based on this response essential control and protection schemes are incorporated with the system. The effectiveness of these schemes is also verified by MATLAB simulation.